MACRONUTRIENTS OMISSION AND THE GROWTH AND NUTRITIONAL STATUS OF ELEPHANT GRASS (CV. MOTT) GROWING IN NUTRIENT SOLUTION - AVALHAES, Cíntia Carla; PRADO, Renato de Mello; ROZANE, Danilo Eduardo; ROMUALDO, Liliane Maria; CORREIA, Marcus André Ribeiro (Scientia Agraria, 2009)
The objective of this work was to evaluate the effect of omission of macronutrients in the growth and the nutritional state of elephant-grass plants (Pennisetum purpureum Shum cv. Mott). The experiment was developed in the FCAV/UNESP, in Jaboticabal-SP,Brazil, using nutrient solution. The experimental design was completely randomized blocks, with seven treatments (the complete solution proposed by Hoagland & Arnon (1950) and the individual omission of N, P, K, Ca, Mg and S, in these solution), in three repetitions. Pre-germinated plants were placed in pot (5 dm3), containing the nutrient solution, which was aerated constantly during the experimental period and the respective treatments, with three replications each. Weekly, the height of the plants, the leaf number, apex diameter and number of tillers were evaluated as well as plant nutritional state. The omission of N, P, K, Ca, Mg and S limited the production of dry weight of shoot the elephant grass, compared to the full treatment. The deficiency of a macronutrient, in addition to promoting reduction of its content in the shoot, resulted in reducing the accumulation of most macronutrients, with resultant morphological changes, translated as characteristic symptoms of deficiency.